Pharmacy Students’ perceptions on distance learning: A case of COVID-19 - Yumrukaya, Leyla; Altınsoy, Gizem Nur; Yeğenoğlu, Selen (Hacettepe University Journal of the Faculty of Pharmacy, 2024)
Online distance learning systems gained importance during school closures all over the world after the COVID-19 outbreak. Pharmacy schools in Türkiye were also affected by these changes and educational activities which shifted to online distance education. In this study, we aimed to evaluate the attitudes of pharmacy students concerning distance education during the pandemic regarding their gender, infrastructural issues, having separate rooms, classes, residency areas and the number of theoretical and applied courses. We conducted an online cross-sectional survey. Thus, a total of 380 pharmacy students participated from pharmacy schools in Türkiye. Perceptions of pharmacy students were compared as per their demographical and educational status. Except gender variable, no significant difference was found among the students. Switching to online distance education formed as a response to the crisis in the pandemic. Although student perceptions from different disciplines have been examined in the existing literature, pharmacy students’ perceptions remained limited. Hence, it is important to understand and point out the students’ perceptions of online distance education in pharmacy schools to be prepared for future emergencies.